'Function First—Be Active, Stay Independent'—promoting physical activity and physical function in people with long-term conditions by primary care: a protocol for a realist synthesis with embedded co-production and co-design. Issue 2 (9th February 2020) - Law, Rebecca-Jane; Williams, Lynne; Langley, Joseph; Burton, Christopher; Hall, Beth; Hiscock, Julia; Morrison, Val; Lemmey, Andrew; Partridge, Rebecca; Lovell-Smith, Candida; Gallanders, John; Williams, Nefyn
Abstract : Introduction: People with long-term conditions typically have reduced physical functioning, are less physically active and therefore become less able to live independently and do the things they enjoy. However, assessment and promotion of physical function and physical activity is not part of routine management in primary care. This project aims to develop evidence-based recommendations about how primary care can best help people to become more physically active in order to maintain and improve their physical function, thus promoting independence. Methods and analysis: This study takes a realist synthesis approach, following RAMESES guidance, with embedded co-production and co-design. Stage 1 will develop initial programme theories about physical activity and physical function for people with long-term conditions, based on a review of the scientific and grey literature, and two multisector stakeholder workshops using LEGO® SERIOUS PLAY®. Stage 2 will involve focused literature searching, data extraction and synthesis to provide evidence to support or refute the initial programme theories. Searches for evidence will focus on physical activity interventions involving the assessment of physical function which are relevant to primary care. We will describe 'what works', 'for whom' and 'in what circumstances' and develop conjectured programme theories using context, mechanism and outcome configurations. Stage 3 will test and refine these theories through individual stakeholder interviews. The resulting theory-driven recommendations will feed into Stage 4 which will involve three sequential co-design stakeholder workshops in which practical ideas for service innovation in primary care will be developed. Ethics and dissemination: Healthcare and Medical Sciences Academic Ethics Committee (Reference 2018-16308) and NHS Wales Research Ethics Committee 5 approval (References 256 729 and 262726) have been obtained. A knowledge mobilisation event will address issues relevant to wider implementation of the intervention and study findings. Findings will be disseminated through peer-reviewed journal publications, conference presentations and formal and informal reports. PROSPERO registration number: CRD42018103027.